AIRIMAGINATION extending the airline business boundaries. - Taneja, Nawal K. ([S.l.] : ROUTLEDGE, 2022)
Unprecedented social changes, accelerated by facilitating technologies and the COVID-19 pandemic, are calling for airlines to think deeply and non-conventionally on what will be important to existing and new travelers, as they change their lifestyles. New thinking requires airlines to extend the boundaries of their businesses to go beyond their traditional domains. This need goes beyond the renovation and iteration of conventional products to the transformation of products requiring new ideas and ways to scale them. Examples include the development of cost-effective urban air mobility, intermodal passenger transportation, door-to-door travel that is sustainable, and personalized offers. Airimagination: Extending the Airline Business Boundaries raises some thought-provoking questions and provides a direction for practical solutions. For example, what if airlines developed products and services that finally meet end-to-end needs of customers seamlessly by collaborating in the value-adding open ecosystems, using platforms that facilitate effective engagement with both "digital and nondigital" customers and employees in real time and at each touch point? Ironically, the current time is an advantage for some airlines as they already have had to deal with a deep and wide disruption caused by the pandemic, leading operations to start from ground zero. This book, the latest in a long and well-regarded series by Nawal K. Taneja, explores innovative best practices within the airline business world, complemented by numerous insightful perspectives contained in multiple forewords and thought leadership pieces. This book is aimed primarily at high-level practitioners within the airline industry and related businesses.
OCLC-licensed vendor bibliographic record.
Keywords: TRANSPORTATION / Aviation / Commercial; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Development / Business Development; Airlines -- Management